Multiple Genomic Events Altering Hominin SIGLEC Biology and Innate Immunity Predated the Common Ancestor of Humans and Archaic Hominins. (18th June 2020) - Khan, Naazneen; de Manuel, Marc; Peyregne, Stephane; Do, Raymond; Prufer, Kay; Marques-Bonet, Tomas; Varki, Nissi; Gagneux, Pascal; Varki, Ajit
Abstract: Human-specific pseudogenization of the CMAH gene eliminated the mammalian sialic acid (Sia) Neu5Gc (generating an excess of its precursor Neu5Ac), thus changing ubiquitous cell surface "self-associated molecular patterns" that modulate innate immunity via engagement of CD33-related-Siglec receptors. The Alu -fusion-mediated loss-of-function of CMAH fixed ∼2–3 Ma, possibly contributing to the origins of the genus Homo . The mutation likely altered human self-associated molecular patterns, triggering multiple events, including emergence of human-adapted pathogens with strong preference for Neu5Ac recognition and/or presenting Neu5Ac-containing molecular mimics of human glycans, which can suppress immune responses via CD33-related-Siglec engagement. Human-specific alterations reported in some gene-encoding Sia-sensing proteins suggested a "hotspot" in hominin evolution. The availability of more hominid genomes including those of two extinct hominins now allows full reanalysis and evolutionary timing. Functional changes occur in 8/13 members of the human genomic cluster encoding CD33-related Siglecs, all predating the human common ancestor. Comparisons with great ape genomes indicate that these changes are unique to hominins. We found no evidence for strong selection after the Human–Neanderthal/Denisovan common ancestor, and these extinct hominin genomes include almost all major changes found in humans, indicating that these changes in hominin sialobiology predate the Neanderthal–human divergence ∼0.6 Ma. Multiple changes in this genomic cluster may also explain human-specific expression of CD33rSiglecs in unexpected locations such as amnion, placental trophoblast, pancreatic islets, ovarian fibroblasts, microglia, Natural Killer(NK) cells, and epithelia. Taken together, our data suggest that innate immune interactions with pathogens markedly altered hominin Siglec biology between 0.6 and 2 Ma, potentially affecting human evolution.